Seng Zhao’s The Immutability of Things and Responses to It in the Late Ming Dynasty - Liu, Yu (Religions, 2020)
Seng Zhao and his collection of treatises, the Zhao lun, have enjoyed a particularly high reputation in the history of Chinese Buddhism. One of these treatises, The Immutability of Things, employs the Madhyamaka argumentative method of negating dualistic concepts to demonstrate that, while “immutability” and “mutability” coexist as the states of phenomenal things, neither possesses independent self-nature. More than a thousand years after this text was written, Zhencheng’s intense criticism of it provoked fierce reactions among a host of renowned scholar-monks. This paper explores Zhencheng’s main points as well as the perspectives and motives of his principal adversaries in order to shed light on the nature of philosophical discourse during the late Ming dynasty.